Endogenous Innovation Waves and Economic Growth - Rainer Andergassen; Franco Nardini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2002)
We propose a simple model where large innovation waves arise from the endogenous propagation of information around sectors. Innovators of each sector invest in internal R&D and in local search for information. We show that depending on the structural parameters of the single sectors, some of the R&D sectors will engage in local search while others will not. Through localised search for information, technology adopted in certain sectors can be adopted also in other sectors, leading to a large technological correlation, and eventually to long ranged innovation waves. We characterise the endogenous balanced growth path of the economy, and the short run fluctuations around it. The model predicts a linear, positive relationship between the short run fluctuations and the long run growth rate. We test this latter relationship and find that we cannot reject the predictions of the model.
Keywords: 330